The benefits of panel data in consumer expenditure surveys - Christopher D. Carroll; Jonathan A. Parker; Nicholas S. Souleles (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
This paper explains why the collection of panel (reinterview) data on a comprehensive measure of household expenditures is of great value both for measuring budget shares (the core mission of a Consumer Expenditure survey) and for the most important research and public policy uses to which CE data can be applied, including construction of spendingbased measures of poverty and inequality and estimating the effects of fiscal policy.
Keywords: E2; G1; 330; Panel Data; Consumer Expenditure Survey; Survey Methods